2022
DOI: 10.3390/insects13010080
|View full text |Cite
|
Sign up to set email alerts
|

Optimising Vine Weevil, Otiorhynchus sulcatus F. (Coleoptera: Curculionidae), Monitoring Tool Design

Abstract: Vine weevil, Otiorhynchus sulcatus F. (Coleoptera: Curculionidae), is an economically important insect pest of horticultural crops. To identify an effective and reliable monitoring system for adult vine weevil, this study investigated the influence of colour, height and entrance position on the efficacy of a model monitoring tool using modified paper cups as refuges. Vine weevil preferences were determined by the number of individuals recorded within a refuge. When provided with a binary choice between black o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 66 publications
2
11
0
Order By: Relevance
“…For vine weevil, laboratory bioassays have demonstrated that small groups of vine weevil adults preferred dark monitoring tools over white or light-coloured ones. 4 To further explore monitoring tool colour preference and confirm whether black monitoring tools may be used as an effective method to detect this species, this study investigated the efficacy of black monitoring tools under glasshouse conditions. Our results confirm that black monitoring tools are more effective than white ones under field representative environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For vine weevil, laboratory bioassays have demonstrated that small groups of vine weevil adults preferred dark monitoring tools over white or light-coloured ones. 4 To further explore monitoring tool colour preference and confirm whether black monitoring tools may be used as an effective method to detect this species, this study investigated the efficacy of black monitoring tools under glasshouse conditions. Our results confirm that black monitoring tools are more effective than white ones under field representative environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Vine weevil, Otiorhynchus sulcatus Fabricius (Coleoptera: Curculionidae), remains one of the most important pests of horticultural and ornamental crops globally. 4,5 This is largely due to the fact that monitoring is challenging as the larvae feed below ground while the adults are nocturnal, therefore controls are often applied too late to prevent economically significant losses. 5 The importance of correctly timing control applications has increased as vine weevil management has shifted from a reliance on persistent broad-spectrum insecticides to entomopathogenic nematodes (EPNs) and fungi (EPFs) used to target vine weevil larvae.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations